Therapeutic Insights into Low-intensity Vibration for Generating Induced Tumor-Suppressive Cells and Modulating the Bone Microenvironment - Xue Xiong; Qingji Huo; Changpeng Cui; Uma K. Aryal; BonHeon Ku; Chin-Suk Hong; HeeChang Lim; Jing Liu; Andy Chen; William R. Thompson; Bai-Yan Li; Xue-Lian Li; et al. (Engineering)
Bone frequently serves as a metastatic site for breast and prostate cancers. Given the potential of low-intensity vibration (LIV) to increase bone health and reduce cancer risk, this study investigated the impact of LIV on cancer cells, as well as noncancer cells such as lymphocytes and peripheral blood mononuclear cells (PBMCs). The results revealed that LIV exposure not only suppressed cancer cell migration but also triggered the generation of induced tumor-suppressing (iTS) cells. Conditioned medium (CM) derived from LIV-treated PBMCs shrank freshly isolated breast and prostate cancer tissues, and when CM was combined with a chemotherapeutic agent, additional antitumor effects were observed. Notably, iTS cell-derived CM hindered the maturation of the receptor activator of nuclear factor-kappa B ligand (RANKL)-stimulated bone-resorbing osteoclasts while promoting the differentiation of bone-forming osteoblasts. Intriguingly, the anticancer effects induced by LIV were replicated by simply shaking a cell-containing tube with a regular tube shaker. Using mass spectrometry-based proteomics, this study revealed enrichment of tumor-suppressing proteins, including enolase 1, moesin (MSN), and aldolase A (ALDOA), which are commonly found in oncogene-activated iTS cells, in LIV-induced CM. Sad1 and UNC-84 domain containing 1 (SUN1), a core component of the linker of the nucleoskeleton and cytoskeleton (LINC) complex, exhibited heightened expression, notably enhancing the response of lymphocytes to LIV. An ex vivo bone cancer model further demonstrated the potent anticancer effects of lymphocyte-derived CM. In conclusion, this study underscores the pivotal role of LIV in preventing bone loss in the tumor microenvironment.